Analysis of Public Policy Implementation in Poverty Alleviation in the Digital Era: A Case Study of Social Assistance Programs in Indonesia - Anggia Ramadhan; Annisa Ilmi Faried; Kristine Krismonita Sinaga (International Journal of Management, Economic and Accounting, 2026)
Digital transformation has changed the way public policy is implemented in Indonesia, including in efforts to alleviate poverty through social assistance programs. This article aims to analyze the implementation of public policies in poverty alleviation in the digital era, with a case study on the national social assistance program for the period 2021–2026. The study uses a descriptive qualitative approach through documentation studies and secondary data analysis sourced from official government institutions and nationally indexed scientific literature. The results of the study show that the national poverty rate has experienced a fairly consistent downward trend, from 10.14 percent in March 2021 to 8.25 percent in September 2025, in line with the strengthening of data governance through the National Socio-Economic Single Data (DTSEN) which integrates Integrated Social Welfare Data, Socio-Economic Registration, and data on the acceleration of extreme poverty elimination. Digitizing aid distribution through artificial intelligence-based verification and Prosperous Family Card accounts has proven to be able to increase the accuracy of targets, speed, and transparency of aid distribution, although it still faces challenges in the form of digital infrastructure gaps, accuracy of population data matching, and limited human resource capacity at the regional level. This article recommends strengthening digital literacy for beneficiary families, accelerating cross-agency data synchronization, and providing a responsive complaint mechanism as a next step in improving digital-based social assistance policies in Indonesia.